Factors Affecting Physical Well-being of Nepalese Children - Yadav, Raj Kumar (Academic Voices: A Multidisciplinary Journal, 2018)
The main objective of this article is to find out the child physical well-belling or nutritional status of children under three years according to demographic, socio-economic, health care, diseases and also standard of living based on primary data. Quantitative and descriptive research design were used to study this article. Out of three hundred ninety five household, one hundred sixty eight respondents (mothers) those whose children seem to be below three years as well as those who seem to be able to give their interview were taken as sample with the help of purposively sampling methods. The data were collected from the field survey in the month of November, 1999 with the help of questionnaire fill-up methods with two Community Health Volunteers (CHVs). All respondents were taken from Yadav, Backward Community like Chamar, Dushadh , Muslim and Amat, and then analyzed. Academic Voices Vol.6 2016: 32-36